Predictors of cerebrovascular event reoccurrence in patients with depression: a retrospective cohort study - Wa Cai; Robert Stewart; Christoph Mueller; Hitesh Shetty; Gayan Perera (BMJ Open)
Objectives To identify predictors of recurrent cerebrovascular morbidity in a cohort of patients with depression and a cerebrovascular disease (CBVD) history.Methods We used the Maudsley Biomedical Research Centre Case Register to identify patients aged 50 years or older with a diagnosis of depressive disorder between 2008 and 2017 and a previous history of hospitalised CBVD. Using depression diagnosis as the index date we followed patients until first hospitalised CBVD recurrence or death due to CBVD. Sociodemographic data, symptom and functioning scores of Health of the Nation Outcome Scales, medications and comorbidities were extracted and modelled in multivariate survival analyses to identify predictors of CBVD reoccurrence.Results Of 1292 patients with depression and CBVD (mean age 75.6 years; 56.6% female), 264 (20.4%) experienced fatal/non-fatal CBVD recurrence during a median follow-up duration of 1.66 years. In multivariate Cox regression models, a higher risk of CBVD recurrence was predicted by older age (HR, 1.02; 95% CI, 1.01 to 1.04) (p=0.002), physical health problems (moderate to severe HR, 2.47; 95% CI, 1.45 to 4.19) (p=0.001), anticoagulant (HR, 1.40; 95% CI, 1.01 to 1.93) (p=0.041) and antipsychotic medication (HR, 0.66; 95% CI 0.44 to 0.99) (p=0.047). Neither depression severity, mental health symptoms, functional status, nor antidepressant prescribing were significantly associated with CBVD recurrence.Conclusions Approximately one in five patients with depression and CBVD experienced a CBVD recurrence over a median follow-up time of 20 months. Risk of CBVD recurrence was largely dependent on age and physical health rather than on severity of depressive symptoms, co-morbid mental health or functional problems, or psychotropic prescribing.